Ways to Activate Youth Employment: Focusing on Government-Funded Job Programs and Promotion of Entrepreneurship - Yong-seong Kim (Korea Development Institute (KDI), 2014)
To help young people find jobs, the government must reallocate financing in government-funded job programs and improve the system for public employment services and start-up new businesses. - Above all else, unemployed young people who are trying to find work should be the main priority for any future employment measures. - It is undeniable that the employment rate for young people in Korea (around 40 percent) is lower than that of advanced economies. - Considering that a disproportionate amount of expenditures go to direct job creation, which tends to benefit people in their 50s, it is recommended that the government begin to reassess how finances are allocated to government-funded job programs. - One recommendation is to operate the SME Internship Subsidy in a way that keeps with its original twofold mission: on one hand, aiding young people in their job search, and on the other, implementing the underused the Employment Promotion Subsidy in a way that complements the Successfully Finding a Job Package II program. - Promoting youth entrepreneurship will require setting up programs that educate students in entrepreneurial preparation and the entrepreneurial spirit, beginning as early as secondary school. A more flexible method should be adopted for selecting the recipients for support, one that includes an assessment of the creativity of the business plan and the potential for development.
Keywords: 330